Alginate as an Efficacious Treatment for GERD Patients: A Literature Review - Ninda Septia Yuspar; Suyata (CV. AKBAR PUTRA MANDIRI, 2025)
Gastroesophageal reflux disease (GERD) is a medical condition defined by the retrograde flow of gastric contents into the esophagus, leading to various symptoms. The principal therapy for GERD consists of proton pump inhibitors (PPIs). Nevertheless, PPIs demonstrate reduced effectiveness in patients with non-erosive GERD or unusual symptoms. Alginates operate by forming a gel